Islamic Worldview sebagai Fondasi Etika dan Spiritualitas Muslim di Era Modern - Wauran, Meissara Putri Andannari; Sumiran, Sumiran (Lembaga Yasin AlSys, 2025)
The Islamic worldview holds a central role in shaping the ethical and spiritual dimensions of the Muslim community, particularly amid the currents of modernity and globalization, which often emphasize materialistic and secular values. This study aims to analyze the role of the Islamic worldview as a foundational basis for cultivating strong ethical and spiritual awareness among Muslims. A qualitative approach was employed through library research, critically analyzing classical and contemporary Islamic literature as well as relevant scholarly works. The findings reveal that the Islamic worldview—rooted in the principles of tauhid, Divine revelation, and the ethics of the Prophet Muhammad (SAW)—serves as an integrative framework for restoring and reinforcing the ethical and spiritual dimensions of Muslim life. The study concludes that the internalization of the Islamic worldview within education systems, religious outreach (dakwah), and social policy is essential for strengthening Muslim identity and addressing the moral crises of the contemporary era. The implications highlight the urgency of adopting the Islamic worldview as an ideological foundation to confront the complex ethical and spiritual challenges of modern life.